Mitral Valve Syndrome in older patients with and without depression: A cross-sectional study - D’Onofrio, Grazia D’; Dagostino, Mariangela Pia; Addante, Filomena; Ciccone, Filomena; Longo, Maria Grazia; Pacilli, Michele; Sancarlo, Daniele; Lauriola, Michele; Cascavilla, Leandro; Greco, Antonio (Journal of Cardiovascular Medicine and Cardiology, 2021)
Study aim was to determine whether Late Life Depression (LLD) is associated with Mitral Valve Syndrome (MVS) presence, and to assess direct proportionality between MVS and LLD severity. A total of 504 consecutive patients (M=260, F=244; Mean Age 79.74±7.83, range=60-98) were included and divided in 2 groups: 1) 360 patients with LLD and MVS (Group 1), and 2) 144 patients without LLD and with MVS (Group 2). All patients were assessed by Doppler echocardiography, complete standardized Comprehensive Geriatric Assessment (CGA) [including basal/instrumental Activities of Daily Living (ADL/IADL), Short Portable Mental Status Questionnaire (SPMSQ), Cumulative Illness Rating Scale Comorbidity Index (CIRS-CI), Mini Nutritional Assessment (MNA), Exton-Smith Scale (ESS), medication use and social aspects], Mini Mental State Examination (MMSE), Clock Drawing Test (CDT), and Frontal Assessment Battery (FAB). Group 1 were more females (p<0.0001), showed higher cognitive damage (MMSE: p=0.001) and a major impairment in several CGA domains: ADL (p<0.0001), IADL (p<0.0001), SPMSQ (p=0.003), CIRS-CI (p=0.003), MNA (p<0.0001), ESS (p<0.0001), and medication number (p=0.002). Group 2 were more no smokers (p=0.030). Group 1 were more without hypertension (p=0.036), dyslipidemia (p=0.025), and diabetes (p=0.048). Patient groups did not differ in other parameters. Significant association between MVS severity and LLD severity showed (OR = 2.140, CI 95% = 1.261-3.630, p = 0.005). LLD patients had higher interventricular septum values (p=0.030), progressively increased with LLD severity (p=0.039). Subjects with LLD and MVS were more implicated in cognitive, functional, clinical and nutritional aspects. LLD severity seems to be associated to MVS severity.